QUILLAMACHAY: A CENTER OF ROUTE ART IN ACOBAMBA, HUANCAVELICA - Ruiz Estrada, Arturo (2000)
Quillamachay is an archeological site. Located in punas of Huancavelica between Mancaro river and Acobamba city. It has been discovered a big number of rock representation in this place which magnitude and characteristics offer us information of eminent imporcance to understand the process of human population not only in Acobamba province but in che Central Andes of Peru. In results of archeological survey done in Quillamachay is presented in chis artide, analyzing site characteristics, nature of the evidences and potential information that is conserved there.